1987
DOI: 10.1101/gad.1.8.808
|View full text |Cite
|
Sign up to set email alerts
|

Distinct factors with Sp1 and NF-A specificities bind to adjacent functional elements of the human U2 snRNA gene enhancer.

Abstract: The enhancer regions of mammalian and avian U1 and U2 small nuclear RNA (snRNA) genes are unusual in containing the sequence GGGCGG (GC-box) immediately upstream from the sequence ATGCAAAT (octamer). We made point mutations in the human U2 snRNA enhancer and tested them for the ability to direct U2 transcription in HeLa cells, as well as for the ability to form complexes with factors present in HeLa cell nuclear extracts. We show that neither the GC-box nor the octamer alone is sufficient for enhancer activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
78
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 45 publications
0
78
0
Order By: Relevance
“…The ubiquitously expressed protein octamer 1 (Oct-1) is a transcription factor having remarkably flexible DNA-sequence recognition properties. Oct-1 has been found to be involved in stimulating RNA-polymerase-I1 transcription of cellular genes that are constitutively active (Mattaj et al, 1985;Ares et al, 1987), cell-cycle regulated (LaBella et al, 1988), tissue-specific (LeBowitz et al, 1988;Johnson et al, 1990;Kemler et al, 1991) or developmentally regulated (Zwartkruis et al, 1992). It has also been shown to be involved in RNA-polymerase- Oct, octamer; POU, Pit-l-Oct-l-Unc-l ; ds, double-stranded.…”
mentioning
confidence: 99%
“…The ubiquitously expressed protein octamer 1 (Oct-1) is a transcription factor having remarkably flexible DNA-sequence recognition properties. Oct-1 has been found to be involved in stimulating RNA-polymerase-I1 transcription of cellular genes that are constitutively active (Mattaj et al, 1985;Ares et al, 1987), cell-cycle regulated (LaBella et al, 1988), tissue-specific (LeBowitz et al, 1988;Johnson et al, 1990;Kemler et al, 1991) or developmentally regulated (Zwartkruis et al, 1992). It has also been shown to be involved in RNA-polymerase- Oct, octamer; POU, Pit-l-Oct-l-Unc-l ; ds, double-stranded.…”
mentioning
confidence: 99%
“…The basic enhancer unit of the human U2 snRNA gene contains Spl binding sites combined with an octamer sequence (Janson et al, 1987(Janson et al, , 1989Ares et al, 1987). Transient expression experiments in HeLa cells have shown that there is an absolute requirement of the octamer motif for U2 transcription (Ares et al, 1987;Janson et al, 1989). Although an Spl binding site alone is unable to stimulate transcription, its deletion results in a 5-fold reduction in transcription (Janson et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription of human U2 genes is controlled by a proximal sequence element (PSE) and a distal sequence element (DSE) which is also called the U2 enhancer (Westin et al, 1984;Ares et al, 1985;Mangin et al, 1986; for review see Dahlberg and Lund, 1987). The basic enhancer unit of the human U2 snRNA gene contains Spl binding sites combined with an octamer sequence (Janson et al, 1987(Janson et al, , 1989Ares et al, 1987). Transient expression experiments in HeLa cells have shown that there is an absolute requirement of the octamer motif for U2 transcription (Ares et al, 1987;Janson et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…U2 snRNA'genes are transcribed by RNA polymerase II (4,5), and the transcription is dependent on a distal enhancer that functions in conjunction with a proximal sequence element (PSE), located 50-60 base pairs (bp) upstream of the cap site (6)(7)(8)(9)(10). It has been shown (11,12) that the U2 enhancer includes one so called octamer motif ATGCAAAT (13), which is the binding site for the transcription factor OTF-1 in nonlymphoid cells (14), and three binding sites for the ubiquitous transcription factor Spl (15,16). A previous characterization of the U2 enhancer revealed a nonadditive functional cooperation between the OTF-1-and the adjacent Spl-binding sites (17).…”
mentioning
confidence: 99%